Pengaruh Tanggung Jawab dan Keadilan Terhadap Kepuasan Pembeli (Studi Kasus PT. Mitra Pinastika Mustika Gresik) - Faizin, Muhammad; Alhidayah, Rita (Universitas Trunojoyo Madura, 2024)
This study aims to find out: (1) The effect of responsibility on customer satisfaction at PT. Mitra Pinastika Mustika Kebomas Gresik. (2) Effect of justice on consumer satisfaction at PT. Mitra Pinastika Mustika Kebomas Gresik. (3) The effect of responsibility and justice simultaneously on cunsumer satisfaction at PT. Mitra Pinastika Mustika Kebomas Gresik. This study uses a quantitative approach, with the research instrument in the form of a questionnaire. This study randomly collected 70 respondents. Test the validity of the instrument using the product moment while the reliability test uses Cronbach Alpha. The analysis technique used is hypothesis testing. The results of the study found that (1) the variable responsibility (X1) partially had a significant effect on customer satisfaction (Y) as evidenced by the value obtained by tcount X1 of 7.411 and ttable of 1.667. (2) responsibility variable (X2) partially has a significant effect on cunsumer satisfaction (Y) as evidenced by the value obtained by tcount X2 of 4.936 and ttable of 1.667. While the variables of responsibility (X1) and justice (X2) simultaneously have a significant influence on cunsumer satisfaction (Y). This is evidenced by the Fcount value of 85.862 Ftable of 3.13. Keywords: Responsibility, Justice, Consumer Satisfaction